Effects of second responder programs on repeat incidents of family abuse: An updated systematic review and meta‐analysis. Issue 1 (28th January 2022) - Petersen, Kevin; Davis, Robert C.; Weisburd, David; Taylor, Bruce
Abstract: Background: Family abuse is a recurrent phenomenon within a select population of households. This form of abuse can include any physical or psychological harassment that occurs between family or household members, and often involves complex mental and emotional issues that are resistant to intervention. Traditional criminal justice strategies for combating this issue have evolved over time but have frequently demonstrated limited success. Within the past few decades, multiagency programs to address repeat family abuse have gained popularity. One such program, termed "second responders, " teams police officers with social service workers, victim advocates, or counselors to conduct follow‐up visits with victims of family abuse following a complaint. Second responders seek to educate victims about the cyclical nature of family abuse, engage in safety planning, and/or provide service referrals. These interventions are based on the premise that victims are more likely to be receptive to crime prevention opportunities immediately following victimization. Second responder interventions have received support from the US Department of Justice and their adoption has spread in both the United States and internationally, however, there remains little conclusive evidence on their effects. Objectives: To update and extend the findings of the prior second responders systematic review and meta‐analysis by synthesizing the results of published and unpublished second responder evaluations through October of 2021. This review also examines the use of victim services as a secondary outcome and incorporates a number of additional moderator analyses. Search Methods: The Global Policing Database (GPD), a repository of all experimental and quasi‐experimental evaluations of policing interventions conducted since 1950, was searched using keywords related to second responder interventions and repeat family violence from 2004 to December 2019 (https://gpd.uq.edu.au/s/gpd/page/about ). This search was also supplemented with additional strategies, such as reference harvesting of prior reviews, searching 2020 and 2021 volumes of leading academic journals, reviewing the reference lists of eligible studies, searching additional gray literature repositories focused on domestic violence, and consulting with eligible study authors. Selection Criteria: Eligible studies were required to include a treatment group that received the second responder intervention and a comparison group that did not. Assignment to these conditions could be either experimental or quasi‐experimental, but quasi‐experimental studies were required to use either matched comparison groups or multivariate analysis methods to control for confounding factors. Eligibility was limited to studies reporting on at least one measure of repeat family abuse, such as intimate partner violence, elder abuse, or general family abuse. Measures of repeat abuse could be based on either official (i.e., police data) or unofficial (i.e., victim survey data) data sources. Data Collection and Analysis: Five new studies were identified between 2004 and 2019, all of which contained sufficient data for the calculation of at least one effect size. Along with the 10 studies included in the prior review, a total of 15 studies and 29 distinct effect sizes were analyzed across three outcome constructs. Effect sizes were calculated as logged odds ratios and results were synthesized using random effects models with restricted maximum likelihood estimation. Final results were exponentiated to represent the percentage point difference in the odds of a given outcome for treatment groups relative to control groups. Risk of bias was assessed using items adapted from the Cochrane Risk of Bias tools for experimental and quasi‐experimental studies. Eligible studies were generally considered to be of low risk of bias, however, issues with survey success/contact rates and the analytical approaches to these problems led to concern in several studies. Results: These analyses suggest that second responder interventions produced no significant effects on either police or victim‐reported measures of repeat family abuse, in aggregate. However, findings from the more rigorous experimental studies indicated that second responder interventions were associated with a statistically significant 22% (95% confidence interval [CI] [1.04, 1.43]) increase in the odds of a police‐reported repeat family abuse incident, with no significant variability in individual study results. Additionally, studies that measured the use of victim services as a secondary outcome were associated with a statistically significant 9% (95% CI [1.02, 1.16]) increase in the odds of service use for treatment groups relative to control groups. Several study characteristics also proved to be important moderators of treatment effects. Increases in the speed of the second response were associated with significant decreases in the odds of a victim‐reported repeat incident, and studies that measured repeat family abuse using households were associated with significantly higher odds of a police‐reported repeat incident, compared to studies that used the same victim or victim/offender pairing more generally. Authors' Conclusions: Second responder interventions are undoubtedly appealing based on their logic and intentions. Yet, well‐intentioned programs with sound logic can still backfire, and the results of this updated review provide evidence that may be suggestive of a backfire effect. Even so, any firm conclusions from this review are limited by a lack of knowledge on the mechanisms operating in between the implementation of the second response intervention and the observed effects, as well as the small sample sizes involved in many analyses. While it seems clear that these programs are not producing any broad reductions in self‐reported victimization, the increase in police‐reported violence seen in experimental studies could indicate either a true increase in abuse or an increased willingness to call the police. The lack of observed impact on victim‐reported violence would suggest the latter, but without more specific measures, such conclusions should be avoided. If these results are indicative of increased reporting, however, many may consider this a desirable outcome, particularly given the often‐underreported nature of family abuse and the potential for increased reporting to lead to long‐term reductions in abuse. Furthermore, these results provide an indication that second responder programs can produce other intended effects, such as increasing the retention of victim services, and that the specific characteristics of these interventions may moderate their effects. It is unclear why elements such as the immediacy of the second response or the unit of analysis being evaluated would impact study results, but these observations are consistent with the theory that domestic violence interventions must capitalize on short windows of opportunity and create separation between victims and offenders to reduce exposure and subsequent victimization. This potential indicates a need for more research on second responder programs, but specifically research that examines these moderating characteristics and mechanisms. Even in light of this potential, second responder programs do not, on average, appear to reduce the prevalence of repeat family abuse. Given the presence of alternative (and possibly more effective) domestic violence interventions that now exist (e.g., Safe Dates, Shifting Boundaries, Green Dot, etc.), it seems that policymakers may wish to look elsewhere for efforts to reduce family abuse.